Penguatan Ekosistem UMKM untuk Meninngkatkan Pendapatan UMKM di Provinsi Sumatera Utara - Ayu Angelina Pasaribu; Herry Daniel Laurent Marpaung; Yosie Gabriela Panjaitan; Lestari Sihite; Fajar Solidman Larosa (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role in accelerating regional economic growth and improving community welfare. However, MSMEs in North Sumatra Province continue to face various challenges, particularly limited access to capital, low adoption of digital technology, and insufficient business assistance. This community service program aims to strengthen the MSME ecosystem through integrated empowerment initiatives, including facilitating access to financing, enhancing the use of internet-based technologies, and improving the capacity of MSME actors. The methods applied include business mentoring, training activities, and analysis of MSME performance in both short-term and long-term perspectives. The results indicate that expanded access to capital and increased adoption of digital technology contribute positively and significantly to MSME income growth in both the short and long term. Interestingly, the absence of guidance, training, and extension services shows a positive correlation with income in the short term but has a significant negative impact on business sustainability and stability in the long term. Furthermore, reliance on bank loans consistently demonstrates a significant negative effect on MSME performance across both analytical periods. These findings highlight the importance of building a sustainable MSME ecosystem through continuous mentoring, improved financial literacy, and adaptive digital transformation to ensure long-term business resilience.